Control of Violence
XVI, 622 p.
Keywords: Modern societies are increasingly confronted with forms of violence that appear unpredictable and uncontrollable. Are the existing control regimes such as police, state surveillance institutions, and legal systems able to effectively contain phenomena such as school shootings, terrorism, or violence in fragile states, and what would help them become more effective? What is the relationship between state rule and self-control in limiting violence? Taking an historically and internationally comparative perspective, the contributors to this innovative book examine these violent phenomena as well as the preconditions and mechanisms of their control. Taking into consideration the fundamentally ambivalent character of control, they explore how institutions and strategies of control retroact on and thus re-shape societies. Moreover, they address general aspects of violence control in modern societies such as the concept of individual self-control, the impact of changing social institutions and the role of religion. The contributions to this volume explore violence on the micro-, meso-, and macro-levels of social organization, creating a cohesive theoretical framework for understanding violence on each of these levels. Control of Violence in Modern Societies will be of great interest to researchers studying violence, particularly to those studying the phenomenon in a global context, be it from a criminological, a sociological or from a public health perspective.